Characterization of the complete chloroplast genome sequence of Anisodus acutangulus (Solanaceae). Issue 1 (2nd January 2020) - Tian, Xing; Bai, Ji-Qing; Yang, Cong-Wei; Zhang, Ying-Min; Li, Guo-Dong
Abstract: Anisodus acutangulus is a Solanaceae perennial plant, which is endemic to China and classified as an endangered species. In this study, we have sequenced the complete chloroplast genome of A. acutangulus, which is 156, 079 bp in length, containing a large single-copy (LSC) region of 86, 526 bp, a small single-copy (SSC) region of 17, 741 bp and comprises a pair of inverted repeat regions (IRs) of 25, 906 bp. Totally 134 genes were annotated, including 87 protein-coding genes, 39 tRNA genes, and 8 rRNA genes. Its overall GC content is 37.6%. Phylogenetic analysis using total chloroplast genome DNA sequence of 21 species revealed that A. acutangulus was closely related to Hyoscyamus niger with 100% bootstrap value.